Security mechanism in computer network environment: A study of adoption status in Malaysian company - Darmawan, N.; Ooi, Keng Boon; Chong, Alain Yee Loong; Venggadasallam, V. (Asian Network for Scientific Information, 2009)
The principle objective of this study was to examine the computer network security level of Malaysian companies. Original research using a self-administered questionnaire was distributed to 300 Malaysian companies. Data were analyzed by employing descriptive statistics. In general the adoption level of network security tools in Malaysia is still considered low with an average mean of 3.22. Based on the tools adopted, most of the companies are using common network security tool such as antivirus as their main protection for their computers. Tools that have lower adoption include vulnerability scanner and packet crafting tool. This research enables company to have a better understanding of the network security tools usage in Malaysian companies. This research has addressed previous lack of study in the examination of company’s security level among Malaysian companies. Information Technology (IT) security personnel in Malaysia will also be able to use this result as a guide as to what type of network security tools is generally being employed among their peers. 3.22 of average mean considered low for the security adoption level in Malaysia, it is necessary to the companies to put more focus on this security mechanism field.